Impact of the Purification Process on the Spray-Drying Performances of the Three Families of Lipopeptide Biosurfactant Produced by Bacillus subtilis - Vassaux, Antoine; Rannou, Marie; Peers, Soline; Daboudet, Théo; Jacques, Philippe; Coutte, François (Frontiers in Bioengineering and Biotechnology, 2021)
Lipopeptides produced by Bacillus subtilis display many activities (surfactant, antimicrobial, antitumoral), which driven them as interesting compounds in a wide range of applications. During the past years, several processes have been developed to enable their production and purification with suitable yield and purity. The already implemented processes mainly end by a critical drying step which is currently achieved by freeze-drying. In this study, the possibility to replace this freeze-drying step by a spray-drying one, more suited to industrial applications, was analyzed. After evaluating their thermal resistance, we have developed a spray-drying methodology applicable for the three lipopeptides families produced by B. subtilis: i.e. surfactin, mycosubtilin (iturin family), and plipastatin (fengycin family). For each lipopeptide, the spray-drying procedure was applied at three steps of the purification process by ultrafiltration (supernatant, diafiltered solution, pre-purified fraction). The analysis of the activities of each spray-dried lipopeptide showed that this drying method is not decreasing their antimicrobial and biosurfactant properties. The methodology developed in this study enabled for the first time, the spray-drying of surfactin, without adjuvants’ addition and regardless of the purification step considered. In the case of fengycin and mycosubtilin, only diafiltered solution and purified fraction could be successfully spray-dried without addition of adjuvant. Maltodextrin addition was also investigated as solution for the direct drying of supernatant. As expected, the performances of the spray-drying step and the purity of the powder obtained are highly related to the purification step at which the product was dried. Interestingly, impact of mycosubtilin concentration on spray drying yield was also evidenced.